Drying and Energy Technologies - Delgado, J.M.P.Q.; Barbosa de Lima, A. Gilson; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a comprehensive overview of essential topics related to conventional and advanced drying and energy technologies, especially motivated by increased industry and academic interest. The main topics discussed are: theory and applications of drying, emerging topics in drying technology, innovations and trends in drying, thermo-hydro-chemical-mechanical behaviors of porous materials in drying, and drying equipment and energy. Since the topics covered are inter- and multi-disciplinary, the book offers an excellent source of information for engineers, energy specialists, scientists, researchers, graduate students, and leaders of industrial companies. This book is divided into several chapters focusing on the engineering, science and technology applied in essential industrial processes used for raw materials and products.
1 Drying of Bioproducts: Quality and Energy Aspects.- 2 Intermittent Drying: Fundamentals, Modeling and Applications.- 3 Clay Products Convective Drying: Foundations, Modeling and Applications.- 4 Use of Ultrasound in the Distilled Water Pretreament and Convective Drying of Pineapple -- 5 Drying Process in Electromagnetic Fields.- 6 Heat and Mass Transfer, Energy and Product Quality Aspects in Drying Processes Using Infrared Radiation -- 7 Dynamic Drying Variables Evolution in Membrane Structure.- 8 Technical Innovation in Dehydration Process for Wine Quality -- 9 Production of Energy - The Second Generation Ethanol and Prospects.- 10 Effective modelling of Phenomena in Over-Moisture Zone Existing in Porous Sand Mould Subjected to Thermal Shock -- 11 Optimization of Pulsed Vacuum Osmotic Dehydration of Sliced Tomato.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Building materials; Energy policy; Energy and state; Engineering Thermodynamics, Heat and Mass Transfer; Structural Materials; Energy Policy, Economics and Management; Building Materials